The Roles of School Principal in the Implementation of Character Education at Boarding School - Asmendri, Asmendri (Institut Agama Islam Negeri Imam Bonjol Padang, 2014)
The success or failures of educational institutions in the implementation of character education in boarding schools or madrasah is determined by its leaders.Â The school principal as a leader and educator should be a good model to all teachers and learners in the school. Â In other words,Â he or she will create a healthy school life, conducive and supportive school performance. There are seven principalâs roles in implementing character building the school. He or she should has a clear vision, rely on more collaborative approach,Â responsive and proactive in responding to what is happening outside of school, be consistent in enforcing the rules, be active, give Â many social rewards, and create a variety of rides or activities that can develop pro-social skills and devotion of students.